If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -4 = -13 Reorder the terms: -4 + -3x = -13 Solving -4 + -3x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3x = -13 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = -13 + 4 -3x = -13 + 4 Combine like terms: -13 + 4 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| -6x-9=-3x+0 | | v+5=9 | | 8(8n-8)+8=232 | | 7x+19=6x+25 | | -5x-8x=13 | | 7-10x=107-38x | | 261+21=4x+14x | | x+15=3x-5 | | -10+6n=1-5n | | 9x+5-4x-9=2x+3x-7 | | -5-z=17 | | 12x-28=6x+12 | | -3y+8=29 | | 6+n=3 | | 97=-6x-6x+1 | | 3-3y=11 | | 2f+3f=5/6 | | p+10=s | | 42-6y=0graph | | 2(4b+1)=b+16 | | 35.1x+24.5-44.6x-41.6= | | -1/9b=-12 | | x^4+2*x^2-4*x+1=0 | | 3=a/5+1/2 | | 12x-3-(23x-48)+(x+93)=58x-(24x-44)+6 | | 5x/2= | | 12x^3y+104x^2y-36xy=0 | | 2/3+5c=-8 | | 5x^2+100x+3=0 | | x^2+x+3.25=0 | | K/-3-2=-20 | | 11=-5k-2 |